Twofold rattling mode-induced ultralow thermal conductivity in vacancy-ordered double perovskite Cs2SnI6. Issue 26 (11th March 2022) - Jong, Un-Gi; Kim, Yun-Sim; Ri, Chol-Hyok; Kye, Yun-Hyok; Pak, Chol-Jin; Cottenier, Stefaan; Yu, Chol-Jun
Abstract : Using self-consistent phonon calculations, we reveal that strong anharmonicity and twofold rattling modes of Cs2 SnI6 induce an ultralow thermal conductivity of 0.11 W m −1 K −1 at 300 K, rarely expected of simple and single-crystalline solids. Abstract : We report a first-principles study of lattice vibrations and thermal transport in Cs2 SnI6, the vacancy-ordered double perovskite. Twofold rattlers of Cs atoms and SnI6 clusters in Cs2 SnI6, being different from CsSnI3 with only Cs atom rattlers, largely scatter heat-carrying acoustic phonons strongly coupled with low-lying optical phonons and lower phonon group velocity. Using renormalized phonon dispersions at finite temperatures, we reveal that anharmonicity and twofold rattling modes induce an ultralow thermal conductivity at room temperature.